Investigation of Attitudes Towards Cancer Screening of Patients Applying to Hospital Outpatient Clinics - Şule Can; Şevval İrem Dalcalı; Bilge Macit; Meftun Akgün; Hatice Demirdağ (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: This study aimed to investigate the attitudes of individuals applying to hospital outpatient clinics toward cancer screening and the factors affecting them.Method: This study is a cross-sectional descriptive study. The study sample consisted of 348 individuals aged 30-70 years who applied to the outpatient clinics of two city hospitals located on the Anatolian and European sides of Istanbul. The data were collected by face-to-face interviews using Personal Information Form and Attitudes Towards Cancer Screenings Scale. Statistical analyses were performed using SPSS (IBM SPSS Statistics 27) package programme. Results: It was determined that 72% of the individuals who participated in our study knew about cancer screening and 43.9% had had it before. The most common reasons for not having cancer screening were thinking that the person was healthy and lack of information. The mean score of the attitude towards cancer screening scale was 94.12± 17.64. It was determined that attitudes towards cancer screening differed according to age, history of cancer, family/neighborhood history of cancer, having information about cancer screening, having regular screening, and wanting to have screening (p<0.05). Conclusion: The attitude of the individuals participating in the study towards cancer screening is above average. However, more than half of the individuals have never had cancer screening. Informing and raising awareness about cancer screening at both individual and social level may increase the frequency of participation in screening.